2003
DOI: 10.1097/01.lab.0000085189.47968.f8
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin Reductase 1 Expression in Colon Cancer: Discrepancy between In Vitro and In Vivo Findings

Abstract: SUMMARY:Thioredoxin and thioredoxin reductase 1 (TR1) are redox proteins that have been implicated in cellular events such as proliferation, transformation, and apoptosis. Analysis of the expression and localization of TR1 in different normal and cancer cell lines and in colon tissues (normal, neoplastic, or inflamed) was performed using reverse transcription-PCR and in situ hybridization. TR1 mRNA was expressed in all analyzed tissues with TR mRNA-positive cells restricted to the stroma of colon crypts, partl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…TrxR is overexpressed in many cancer cell lines, such as breast, renal, and colon (34,35), and its inhibition prevents cancer cell growth in vivo (35). Although the data in this study seem to be in contrast with what has been shown previously, the differing effects are not surprising because the function of cancerous or transformed cells often does not resemble that of a healthy EC.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…TrxR is overexpressed in many cancer cell lines, such as breast, renal, and colon (34,35), and its inhibition prevents cancer cell growth in vivo (35). Although the data in this study seem to be in contrast with what has been shown previously, the differing effects are not surprising because the function of cancerous or transformed cells often does not resemble that of a healthy EC.…”
Section: Figurementioning
confidence: 99%
“…Se is essential for the activity of TrxR; adding 1 µM Se to cell culture media is sufficient to increase the activity of this enzyme in normal and cancer cell lines up to 40-fold (29,32,33). The expression of TrxR and its main substrate thioredoxin (Trx) are increased in many cancer cells and transformed cell lines (34,35); however, the manner in which decreased TrxR activity in EC may affect critical functions important for cancer progression has yet to be examined extensively. ECs are essential to the angiogenic process, so it is crucial to understand the regulation of TrxR, VEGF, and VEGF receptors by these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Another illustrative example is the Michael addition-mediated covalent binding of curcumin at the tyrosine kinase domain of ErbB-2, which leads to intracellular depletion of the curcuminErbB-2 complexes via mainly nonproteasomal and nonlysosomal pathways . Inasmuch as COX-2, lipoxygenases, and ErbB receptors are expressed in intestinal mucosa (Kawajiri et al, 2002;Sagiv et al, 2007;McElroy et al, 2012) and TrxR1 is present in the colon (Lechner et al, 2003), the abovementioned processes negatively affect the systemic disposition of curcumin and expand the variety of curcumin metabolites in the intestinal mucosa.…”
Section: Tablementioning
confidence: 99%
“…In fact, Trx1 expression level positively correlates with high proliferation capacity, low apoptosis, elevated metastasis (21), increased drug resistance (22), and decreased patient survival (23). By contrast, the role of Txnrd1 in cancer is less clear (24) and could be tumor origin dependent (20). Txnrd1 inactivation by chemical inhibition (25) or small interfering RNA (siRNA)-mediated knockdown (26)(27)(28) inhibits self-sufficiency of tumor cells, reverts the malignant phenotype, and sensitizes tumor cells toward the oxidative stress-inducing agents H 2 O 2 and ionizing radiation (29).…”
Section: Introductionmentioning
confidence: 99%